ADVERTISING AND COMMUNICATION INDUSTRY OF UKRAINE: INFLUENCE OF MACROENVIRONMENTAL FACTORS - IVANECHKO, Nelia; OKONSKYI, Mykhailo (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article examines changes in the structure of the advertising market and its synergy with Digital. It was established that the structure of the advertising market, as of 2023, consists of four directions: media advertising, marketing services, digital advertising and PR market. In turn, media advertising includes: TV advertising (direct advertising, sponsorship); digital TV; advertising in the press (national, including sponsorship, regional, specialized); radio advertising (national, regional, sponsorship); OOH Media (outdoor advertising, transport advertising, DOOH, Indoor advertising); advertising in cinemas; Digital (Internet) Media advertising. Marketing services include: Trade marketing (Merchandising, Trade promo, Personnel motivation and control programs); Loyalty marketing (Mailing, DB management, Contact Center); Consumer marketing; Event Marketing and Sponsorship. Digital advertising includes: banner advertising, ads in social networks, rich media; digital video, incl. Youtube; search (paid publication in search engines), including part of GDN; influencer marketing and other digital. Quantitative indicators of the advertising market were studied and significant growth of Digital advertising in 2013-2022 was revealed. The influence of macroeconomic factors, in particular, digital technologies, the COVID-19 pandemic, the Russian-Ukrainian war on advertising and communication activities is analyzed. The study showed that the COVID-19 pandemic contributed to the development and increase of market volumes, and the war led to a significant decrease in the quantitative indicators of the media advertising, marketing services and PR market. The digital market also declined, but only to the indicators of the pandemic period. It was established that the technological factor had a significant impact on the advertising market, not only by changing traditional platforms, but also by additional opportunities in the field of production of advertising materials and creativity. The changes in the legislation of Ukraine introducing the norms of the European legislation into the national legislation through the implementation of certain provisions of the EU legislation in the field of audiovisual advertising are indicated.
Keywords: advertising market; Internet; advertising and communication industry; media advertising; marketing services; Digital advertising; PR market